Increased Moral Sensitivity for Outgroup Perpetrators Harming Ingroup Members. (2nd September 2014) - Molenberghs, Pascal; Gapp, Joshua; Wang, Bei; Louis, Winnifred R.; Decety, Jean
Abstract: From an evolutionary perspective, one should be more sensitive when outgroup members attack the ingroup but less so when ingroup or outgroup members fight among themselves. Indeed, previous behavioral and neuroimaging research demonstrated that people show greater sensitivity for the suffering of ingroup compared with outgroup members. However, the question still remains whether this is always the case regardless of who is the agent causing the harm. To examine the role of agency and group membership in perception of harm, 48 participants were scanned while viewing ingroup or outgroup perpetrators intentionally harming ingroup or outgroup members. Behavioral results showed greater moral sensitivity for ingroup versus outgroup victims, but only when the perpetrator was from the outgroup. In support of this finding, fMRI data showed greater activity in left orbitofrontal cortex (OFC) for ingroup victims when they were harmed by outgroup individuals. In addition, effective connectivity analyses documented an increased coupling between left OFC and left amygdala and insula for ingroup harm, when the perpetrator was from the outgroup. Together these results indicate that we are highly sensitive to harm perpetrated by outgroup members and that increased sensitivity for ingroup victims is dependent on who is the agent of the action.